2016
DOI: 10.1016/j.algal.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heterotrophically stressed algae for biofuel production via hydrothermal liquefaction and catalytic hydrotreating in continuous-flow reactors

Abstract: Two algal feedstocks were prepared for direct comparison of their properties when converted to liquid hydrocarbon fuel. The first feedstock was prepared by growing an algal strain phototrophically using a bio-film based approach. The second feedstock employed the same algal strain but was stressed heterotrophically to significantly increase the lipid concentration. The algal feedstocks were converted to liquid hydrocarbon fuels. First, the whole algae (i.e. not defatted or lipid extracted) were converted to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 14 publications
1
34
2
Order By: Relevance
“…The authors however remark that this could be also caused by the fact that oxygen is determined by difference, so this could lead to errors in its determination. Another paper from the same group, authored by Albrecht et al [43], showed similar results on heterotrophically stressed algae biocrude.…”
Section: Bio-crude Upgradingmentioning
confidence: 54%
See 2 more Smart Citations
“…The authors however remark that this could be also caused by the fact that oxygen is determined by difference, so this could lead to errors in its determination. Another paper from the same group, authored by Albrecht et al [43], showed similar results on heterotrophically stressed algae biocrude.…”
Section: Bio-crude Upgradingmentioning
confidence: 54%
“…[42], macroalga Saccharina spp. [44] and Chlorella, with both standard and high lipid content [43]. Some experience was also gained in the processing of agricultural waste, such as grape pomace [45], and of wastewater solids [46].…”
Section: Pilot Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The product values for HTL range from %1.39 to 2.72 $ L À1 for different algal biomass feedstocks. [30,60,93,94] Orfield et al studied an algal biorefinery concept using HTL and reported a product cost of 1.64 $ L À1 . [94] Another HTL study on microalgae using different cultivation systems showed product costs of 1.66-2.20 $ L À1 for biomass costs from 510 to 673 $ t À1 .…”
Section: Product Cost Estimates and Comparison With Other Studiesmentioning
confidence: 99%
“…In addition, the total acid number (TAN) of stabilized biocrude is significantly low; the low TAN will help avoid corrosion during bitumen pipeline transportation. The properties of stabilized biocrude from HTL and of diluents are summarized in Table …”
Section: Stabilized Biocrude As a Diluentmentioning
confidence: 99%